The Need for Evidence Based Nutritional Guidelines for Pediatric Acute Lymphoblastic Leukemia Patients: Acute and Long-Term Following Treatment - Owens, Joyce L. (MDPI, 2013)
High survival rates for pediatric leukemia are very promising. With regard to treatment, children tend to be able to withstand a more aggressive treatment protocol than adults. The differences in both treatment modalities and outcomes between children and adults make extrapolation of adult studies to children inappropriate. The higher success is associated with a significant number of children experiencing nutrition-related adverse effects both in the short and long term after treatment. Specific treatment protocols have been shown to deplete nutrient levels, in particular antioxidants. The optimal nutrition prescription during, after and long-term following cancer treatment is unknown. This review article will provide an overview of the known physiologic processes of pediatric leukemia and how they contribute to the complexity of performing nutritional assessment in this population. It will also discuss known nutrition-related consequences, both short and long term in pediatric leukemia patients. Since specific antioxidants have been shown to be depleted as a consequence of therapy, the role of oxidative stress in the pediatric leukemia population will also be explored. More pediatric studies are needed to develop evidence based therapeutic interventions for nutritional complications of leukemia and its treatment.